Improved alpharetrovirus-based Gag.MS2 particles for efficient and transient delivery of CRISPR-Cas9 into target cells - Yvonne Baron; Johanna Sens; Lucas Lange; Larissa Nassauer; Denise Klatt; Dirk Hoffmann; Marc-Jens Kleppa; Philippe Vollmer Barbosa; Maximilian Keisker; Viviane Steinberg; Julia D. Suerth; Florian W.R. Vondran; et al. (Elsevier, 2022)
DNA-modifying technologies, such as the CRISPR-Cas9 system, are promising tools in the field of gene and cell therapies. However, high and prolonged expression of DNA-modifying enzymes may cause cytotoxic and genotoxic side effects and is therefore unwanted in therapeutic approaches. Consequently, development of new and potent short-term delivery methods is of utmost importance. Recently, we developed non-integrating gammaretrovirus- and MS2 bacteriophage-based Gag.MS2 (g.Gag.MS2) particles for transient transfer of non-retroviral CRISPR-Cas9 RNA into target cells. In the present study, we further improved the technique by transferring the system to the alpharetroviral vector platform (a.Gag.MS2), which significantly increased CRISPR-Cas9 delivery into target cells and allowed efficient targeted knockout of endogenous TP53/Trp53 genes in primary murine fibroblasts as well as primary human fibroblasts, hepatocytes, and cord-blood-derived CD34+ stem and progenitor cells. Strikingly, co-packaging of Cas9 mRNA and multiple single guide RNAs (sgRNAs) into a.Gag.MS2 chimera displayed efficient targeted knockout of up to three genes. Co-transfection of single-stranded DNA donor oligonucleotides during CRISPR-Cas9 particle production generated all-in-one particles, which mediated up to 12.5% of homology-directed repair in primary cell cultures. In summary, optimized a.Gag.MS2 particles represent a versatile tool for short-term delivery of DNA-modifying enzymes into a variety of target cells, including primary murine and human cells.